Employee’s perceptions of internal Corporate social responsible related to satisfaction and loyalty to the organization / Nor Amira Mustafa - Mustafa, Nor Amira (Faculty of Business and Management, 2012)
The research is conduct in order to determine Employee’s perceptions of internal corporate social responsible (CSR) related to satisfaction and loyalty to the organization. A growing number of studies have been done regarding the benefits of CSR. However, most are concerned with the financial and customer perspective; while very little attention has been paid to internal CSR which in this study the internal CSR is the internal stakeholders (employees). Employees play an important role as they act as a scale to measure company success. The success of a company greatly rely upon how well employees are being treated in the organization, therefore employees act as an important stakeholder in the company. The main objective of this study is to identify the most influential factor that contributes to Employee’s perceptions of internal corporate social responsible (CSR) related to the satisfaction and loyalty among employees to their organization. The factors are job satisfaction, organizational culture and organizational commitment. Researcher used questionnaire as a main instrumental in data collection method and it involved 80 respondents. All the data collected will be analyzed using Statistical Package for Social Science (SPSS). In general, the results of this research show that Organizational Commitment is the most influence factor with the employee’s perceptions of internal corporate social responsible (CSR) related to satisfaction and loyalty to the organization. The conclusion for this study is from the outcome from the findings and analysis. Recommendations for future research are also been discussed.